Balancing the Protection of Life and the Prevention of Harm: A Maqāṣid al-Sharīʿah Framework for Pregnancies Resulting from Boko Haram-Induced Rape and Forced Marriage in Nigeria - Ismail Danjuma Yusuf; Fatimah Tanimu Bindawa; Diana Zuhroh (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2026)
Pregnancies resulting from Boko Haram-induced rape and forced marriage in Nigeria present complex legal, ethical, and humanitarian challenges within Islamic law, particularly in balancing the sanctity of human life with the rights and welfare of women affected by conflict-related sexual violence. This study examines the permissibility of abortion in such circumstances through the framework of maqāṣid al-sharīʿah (the objectives of Islamic law). Drawing on a qualitative doctrinal research methodology, the study analyzed the relevant sources of Islamic laws such as the Qur'an, Hadith, classical treatises on fiqh, modern scholarly opinions, and secondary sources discussing abortion, Islamic laws, and the related violence committed by Boko Haram. The study found out that while abortion remains haram (forbidden) under Islamic law based on the maqāṣid principles of protecting life (ḥifẓ al-nafs) and lineage (ḥifẓ al-nasl), there existed some leniency in the Islamic legal laws depending on the stage at which a fetus is located. Applying the maqāṣid framework demonstrates the need to balance fetal rights with considerations of psychological trauma, social harm, human dignity, and public welfare experienced by victims of conflict-related sexual violence. This study recommends the development of a three-stages maqāṣid-oriented Islamic law framework consisting of a pre-ensoulment assessment, post-ensoulment protection, and post-birth provisions.